Πλημμυρισμένες εκτάσεις, λευκοκαλλιέργειες και γεωργικές καλλιέργειες στη λίμνη Αμβρακία - Ε. Παπαστεργιάδου (1998)
Πλημμυρισμένες εκτάσεις, λευκοκαλλιέργειες και γεωργικές καλλιέργειες στη λίμνη Αμβρακία